Perspectives on Integrating Social Capital Resources and Networks into the Multiple Roles of Public Relations - Lai, Cheng-Neng (Advances in Social Sciences Research Journal, 2016)
While the concept of social capital is widely applied in studies relating to politics, economics, and sociology it is rarely adopted in connection with public relations. Social capital underlies the stimulation of individuals’ behaviors and so relates to the establishment of good relationships that public relations also emphasizes. This study explores the connections between the multiple roles that public relation plays and social capital from the perspective of resources and networks. By doing this we anticipate extending research into the operation of public relations.